The Emphasis of Explosive Power, Flexibility, and Motivation Judging from Back Kick Speed on BKMF Athletes - Hanas, Muhammad Yusuf; Suyudi, Imam; Hudain, Muh. Adnan; Ihsan, Andi; Adil, Ahmad (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This research objective is to determine the influence of explosive power, flexibility, and motivation in terms of back kick speed in the pencak silat sport. This research is a type of correlational research. The population of this study was all BKMF pencak silat athletes at Makassar State University, with a total research sample of 15 athletes using the Total Sampling method. The data analysis technique used is a descriptive analysis technique using the SPSS Version 21.00 system at a normal level of α 0.05. Judging from the results of the data analysis, the researcher can conclude that: (1) Explosive power is influenced by motivation in State University BKMF pencak silat athletes Makassar, with a p-value of 0.005. (2) Flexibility is influenced by motivation in Makassar State University BKMF pencak silat athletes with a p-value of 0.004. (3) Explosive power influences the back kick with a p-value of 0.015. (4) Flexibility influences the back kick with a p-value of 0.016. (5) Motivation influences the speed of the back kick with a p-value of 0.001. (6) Leg muscle explosive power through motivation influences the speed of the straight kick with a p-value of 0.000005, and (7) abdominal muscle strength through motivation influences the speed of the straight kick with a p-value of 0.00004.